Predictors of the Intention to Participate in Slum Upgrading Projects: Perceptions of Slum Dwellers in Mauritius. (May 2023) - Swapan, Mohammad Shahidul Hasan; Sadeque, Saalem; Iftekhar, Md. Sayed; Sooben, Neshen
A global shift in urban slum improvement programmes is underway to step beyond the conventional approach by practicing a more participatory approach. Previous studies have found that slum upgrading projects are likely to be ineffective and unsustainable without the active participation of slum dwellers. Therefore, it is imperative to identify the pathways to improve or enhance slum dwellers' participation in slum upgrading projects. Several studies highlight the need to consider socio-psychological attributes of the community. However, empirical evidence of the comparative significance of these attributes in predicting participatory behavioural intention of the slum dwellers has not been previously explored. In this article, we examine the factors that influence slum dwellers' intention to participate in slum upgrading projects in Mauritius, which has been one of the early implementers of UN-Habitat's flagship initiative, Participatory Slum Upgrading Programme. We conducted a household survey in highly dense slum areas in Cité EDC and Barkly. Using the Partial Least Squares Structural Equation Modelling approach to analyse the relationships among the constructs affecting participatory behaviour, we find that enhancement of awareness and trust on authority can promote willingness to participate at a higher level in slum upgrading projects. Such information can be useful to design appropriate pathways to increase effective participation in slum upgrading programmes.